Assessment and Management of Environmental Risks during the Operation of Field Oil and Gas Pipelines - Suleymanov, G.S.; Ismayilova, H.G. (Herald of Azerbaijan Engineering Academy, 2023)
The efficiency of operation of field oil and gas pipelines is determined by the factors of reliability and operation to "failure". To make and implement management decisions aimed at reducing the likelihood of an adverse outcome and minimizing possible losses, it is necessary to classify the operational risks of pipeline systems. The paper considered the issues of classification of operational risks, possible scenarios and damages of negative consequences during the operation of field pipelines. The nature of the change in the probability of an oil spill depending on its degree has been studied. In the paper, for each risk factor, taking into account its value, a strategy for managing individual risks is proposed.